Efektifitas Pijat Kaki Dan Rendam Kaki Dengan Air Jahe Hangat Terhadap Edema Kaki Ibu Hamil Trimester III Di Desa Kertasari Kecamatan Rengasdengklok Kabupaten Karawang - Marina; Astuti , Wiji (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: One of the physical changes during pregnancy is edema in the legs. In Kertasari Village, Kertasari District, in 2022, 60.3% of pregnant women in their third trimester were found to experience physiological leg swelling. Management of feet with physiological edema includes foot massage and hydrotherapy or soaking the feet in warm ginger water. To determine the effectiveness of foot massage and foot soaks in warm ginger water on third trimester pregnant women's foot edema in Kertasari Village, Rengasdengklok District, Karawang Regency Methods: Pre experimental design with one group pretest-posttest design. The samples were 31 pregnant women in the third trimester who experienced leg edema using a total sampling technique. Bivariate analysis used the Wilcoxon test. Results: Univariate research results mean the average leg edema of pregnant women in the third trimester before being given a foot massage and soaking the feet in warm ginger water was 5.26 and afterward was 2.90. The results of the bivariate research showed that the p value = 0.000 Conclusion: There is effectiveness of foot massage and foot soaking in warm ginger water on third trimester pregnant women's foot edema. It is hoped that health workers in dealing with physiological edema in pregnant women in the third trimester are expected to be able to provide complementary midwifery care, one of which is by doing foot massages and doing warm water soaks plus easily available natural ingredients such as ginger to reduce physiological edema